Genetic Variability of TCF4 in Schizophrenia of Southern Chinese Han Population: A Case-Control Study - Yin, Jingwen; Zhu, Dongjian; Li, You; Lv, Dong; Yu, Huajun; Liang, Chunmei; Luo, Xudong; Xu, Xusan; Fu, Jiawu; Yan, Haifeng; Dai, Zhun; Zhou, Xia; et al. (Frontiers in Genetics, 2019)
Objective: Schizophrenia is thought to be a neurodevelopmental disorder. As a candidate risk gene in the development of the central nervous system, transcription factor 4 (TCF4) has been shown to be involved in the pathogenesis of schizophrenia. The aim of our study was to assay the association of TCF4 single nucleotide polymorphisms (SNPs) with schizophrenia and the effect of these SNPs on phenotypic variability in schizophrenia. Method: Four SNPs (rs9960767, rs2958182, rs4309482, and rs12966547) of TCF4 were genotyped in 1137 schizophrenic patients and 1035 controls in a Southern Chinese Han population using the improved multiplex ligation detection reaction (iMLDR) technique. For patients with schizophrenia, the severity of symptom phenotypes was analysed by the five-factor model of the Positive and Negative Symptom Scale (PANSS). Cognitive function was assessed using the Brief Assessment of Cognition in Schizophrenia (BACS) scale. Results: The results showed that the genotypes and alleles of the 4 SNPs were not significantly different between the control group and the case group (all P > 0.05). However, the genotypes of rs4309482 (P=0.04) and rs12966547 (P=0.03) were related to the positive symptoms of the PANSS. In addition, the genotypes of rs4309482 had a significant difference for excitement scores (P=0.04). Conclusion: TCF4 might be a risk factor affecting schizophrenia in a phenotype-specific manner in the Southern Chinese Han population.